The application of graphene for in vitro and in vivo electrochemical biosensing - Janegitz, Bruno Campos (2017)
Advances in analysis are required for rapid and reliable clinical diagnosis. Graphene is a 2D material that has been extensively used in the development of devices for the medical proposes due to properties such as an elevated surface area and excellent electrical conductivity. On the other hand, architectures have been designed with the incorporation of different biological recognition elements such as antibodies/antigens and DNA probes for the proposition of immunosensors and genosensors. This field presents a great progress in the last few years, which have opened up a wide range of applications. Here, we highlight a rather comprehensive overview of the interesting properties of graphene for in vitro, in vivo, and point-of-care electrochemical biosensing. In the course of the paper, we first introduce graphene, electroanalytical methods (potentiometry, voltammetry, amperometry and electrochemical impedance spectroscopy) followed by an overview of the prospects and possible applications of this material in electrochemical biosensors. In this context, we discuss some relevant trends including the monitoring of multiple biomarkers for cancer diagnostic, implantable devices for in vivo sensing and, development of point-of-care devices to real-time diagnostics. (C) 2016 Elsevier B.V. All rights reserved.